Orders-of-magnitude reactivity enhancement in persulfate activation by curvature-dependent oxygenated carbon nanotubes - Xin Yang; Zhongyuan Guo; Pufan Wang; Justin Prabowo; Yangyang Wang; Jiaxiang Chen; Jiacheng Wu; Xinyi Huang; Yichen Feng; Chengli Rong; Fangzhou Liu; Hao Li; et al. (Chemical Engineering Journal, 2026)

Arginine-rich hemp seed globulin-tannic acid non-covalent complexation: Structural compaction, enhanced antioxidant/emulsifying properties, and modulated digestibility - Yu Zhang; Xiao-Dong Tian; Zuo-Xing Di; Hai-Bo Jin; Guang-Xiang He; Suo-He Yang; Rong-Yue Zhang; Lei Ma; Xiao-Yan Guo; Peng-Wei Xu (Food Chemistry, 2026)

TF2A ameliorates lipid metabolism in high fat diet mice as an oxidative derivative of EGCG with altered gut microbiota and hepatic transcriptomic profiles - Yiyun Zhang; Zongzhen Guo; Kefan Wei; Rong Li; Jiaqian Cao; Liang Zhao; Sujing Wu; Caili Feng; Qiliu Jiang; Yong Xue (Food Bioscience, 2026)

Molecular mechanisms of neutron irradiation damage in CL-20: A multiscale modeling approach from collision cascades to real-space defect mapping - Wei-Yi Li; Tao Wang; Rong Liu; Yu-Heng Li; Wan-Xiao Guo; Xi-Yao Yun; Yi-Lin Fang; Jin-Tao Wang; Ning Gao (Chemical Engineering Journal, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Cinnamoylphenethyl amides from fissistigma bracteolatum and their anti-inflammatory activities - Jin-Feng Xue; Yao-Yao Jia; Jing-Wei Lei; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhen-Zhu Zhao; Dong-Rong Zhu; Guo-Sheng Li; Gui-Min Xue (Natural Product Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Crustal melting and evolution during continental collision in the eastern Central Pamir, Tajikistan - Sharifjon Odinaev; Wei Dan; Andrey K. Litvinenko; Jovid Aminov; Murodov Azamdzhon; Xin Ma; Umed A. Yatimov; Shan-Shan Yang; Guo-Rong Tang; Gong-Jian Tang (Lithos, 2026)

Mechanistic insights into triclocarban-induced skin barrier disruption via integrating imaging localization, multi-omics, and network toxicology - Jingwen Zheng; Run Guo; Rong Zhang; Xinyu Liu; Rouyue Guo; Haozheng Li; Juntong Wei; Yuxin Zheng; Hongna Zhang (Environmental Pollution, 2026)

Corrigendum to “Progress in the application of Salmonella vaccines in poultry: A mini review” [Vet. Immunol. Immunopathol. 278(2024), 110855] - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2026)

Os79, a UDP‐Glycosyltransferase, negatively regulates cadmium tolerance and accumulation in rice - Rui Guo; Hao Yu Wang; Chong Wei Zhong; Rong Rong Ma; Jiu Huang; Jin Chen; Xian Jiao Guan; Lu Zheng; Ren Fang Shen; Ming Qing Liu; Xiao Fang Zhu (Journal of Hazardous Materials, 2026)

From gas-liquid to liquid-liquid: A programmable compartmented droplet microreactor under ambient conditions - Gaojian Chen; Duo Wei; Junhao Zhu; Rong Guo; Lingling Ge (Chemical Engineering Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Crotiglianoids A−M, tigliane-type diterpenoids from the seeds of Croton tiglium and their anti-hepatic fibrosis activity - Guang-Hai Zhu; Zhen-Zhou Han; Rong Huang; Li-Fen Ma; Xin-Yi Hu; Fei-Yu Zhang; Yi-Ling Liao; Lu Gan; De-an Guo; Wei Li (Phytochemistry, 2026)

Green derivative synchronous fluorescence spectroscopy approach for rapid quantification of Rhodamine B in food samples - Hong-Jun Liu; Jia-Rong He; Yi-Han Guo; Jia-Lin Li; Wei-Peng Cai; Ping-Ping Wu; Yao-Qun Li (Food Control, 2026)

Mapping the spatiotemporal distributions of terpenoids and coumarins in Ferula ferulaeoides stem by using MALDI-MSI - Xuerui Zhang; Fangwei Diao; Rong Guo; Zibo Wei; Kai Liao; Yun Zhu (Journal of Plant Biochemistry and Biotechnology, 2026)

Hormonally and chemically induced male-to-female sex reversal is independent of Y-chromosome number in common carp - Kuangxin Chen; Yuanqi Guo; Yi Rong; Zhaoxian Li; Mouyan Jiang; Rui Li; Xiya Zhang; Yongming Li; Yulai Wei; Yanlong Song; Ji Chen; Binbin Tao; et al. (Aquaculture, 2026)

Soil organic carbon in arid and humid grasslands of China: Spatial heterogeneity, driving factors, and future changes - Zihan Kan; Mingming Wang; Jiyuan Liu; Shihang Zhang; Wei Hang; Boyi Song; Yongxing Lu; Hao Guo; Xing Guo; Jungang Yang; Xiaoying Rong; Ye Tao; et al. (Science of The Total Environment, 2026)

Mechanisms by Which Humic Acid Reduces Copper Toxicity in Citrus Roots Based on Omics and Physiology - Wei-Tao Huang; Rong-Rong Xie; Liang-Yuan Tong; Tian-Tian Xia; Jiuxin Guo; Ning-Wei Lai; Zeng-Rong Huang; Lin-Tong Yang; Li-Song Chen (Journal of Plant Growth Regulation, 2026)

Optimization of nitrogen-soil microbial interactions to regulate carbon and nitrogen footprints and enhance yield sustainability in maize fields - Tiantian Meng; Jingjing Shi; Xiangqian Zhang; Xiaoyu Zhao; Xiaorong Wu; Meiren Rong; Yanan Liu; Xingxing Guo; Shuli Wei; Yongfeng Ren; Zhanyuan Lu; Jianwei Zhang (Applied Soil Ecology, 2026)

Nitrogen application regulates ecosystem multifunctionality through soil microbial diversity: a quantitative assessment - Tiantian Meng; Yanan Liu; Xiangqian Zhang; Jingjing Shi; Xiaoyu Zhao; Xuanyi Chen; Meiren Rong; Xingxing Guo; Shuli Wei; Jiawei Liu; Zhanyuan Lu (Plant and Soil, 2026)

Pharmaceutical-dominated organic contaminants in plateau lakes: Suspect and non-target screening, PBT risk, and structure-based risk markers - Liben Chou; Wanshu Zhu; Rong Zhang; Jinsha Jin; Kai Huang; Lu Dong; Mengke Jin; Wenrui Luo; Yan Mao; Xiangyi Yu; Haoyue Tan; Jing Guo; et al. (Water Research, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

Establishing one-step hairy root transformation system in safflower using RUBY reporter - Rong Guo; Xuerui Zhang; Xu Jiao; Chunfeng Zhu; Jian Wei; Yun Zhu (Journal of Plant Physiology, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

Cold adaptation strategies of anammox bacteria and the bottleneck of nitrogen removal performance in autotrophic nitrogen removal process treating digested swine wastewater - Ya-hui Wang; Fang-yu Huang; Long-xing Jiang; Rong You; Yun-hong Zhang; Liang-wei Deng; Wen-guo Wang; Lan Wang (Chemical Engineering Journal, 2026)

Automatic Detection of Disaster-Causing Organisms near the Waters of Nuclear Power Plant Based on LiveScope Scanning Sonar Images - Gangyi Yu; Shuo Wang; Wei Liu; Yongjian Xia; Yuchen Guo; Xiaolu Chen; Xueping Wei; Ao Chen; Zehua Lv; Chao Lu; Junbo Zhang; Rong Wan (Journal of Marine Science and Engineering, 2026)
Nuclear power serves as an efficient, clean, and low-carbon energy source that constitutes a significant component of the energy portfolio in numerous countries. Most nuclear power plants are predominantly situated in coastal regions, utilizing seawater as the ultimate heat sink for their cooling systems. Real-time monitoring of marine organism dynamics near water intakes is essential to mitigate the risk of unit shutdowns triggered by outbreaks of disaster-causing organisms (DCOs). This study employed LiveScope scanning sonar videos captured near the Ningde Nuclear Power Plant to develop a dataset for detecting the light spot area of the DCOs. We proposed a directionally optimized model, Bio-YOLO v7, which significantly enhances the detection of small targets in sonar images. The Bio-YOLO v7 model achieved precision, recall, and average precision rates of 85.29%, 83.28%, and 81.49%, respectively, demonstrating superior performance in identifying DCOs near the intakes of nuclear power plant. The light spot size of the DCOs exhibited significant periodic variations, serving as a crucial indicator for forecasting outbreak events.

Unlocking a new application of coal and biomass co-ethanolysis: high-performance supercapacitor based on N/O self-doped hierarchical porous carbons - Li Li; Yu-Fan Ren; Chang-Wang Shao; Long-Yu Zhang; Guo-Rong Qi; Xing-Shun Cong; Xian-Yong Wei; Zi-Chun Fan; Xiao-Yu Zhang (Fuel, 2026)

Boosting surface basicity of In2O3 aerogel for high-performance H2S sensors via an in-situ annealing strategy of carbon-composited In(OH)3 - Zheng Yang; Qian Rong; Wei Zhang; Qi Xu; Mengen Shao; Jiang Li; Chunchang Wang; Youmin Guo (Chemical Engineering Journal, 2026)

Low-δ18O magmas at Batur, Indonesia: Evidence for slab-window melting beneath arc volcanoes - Guo-Rong Tang; Wei Dan; Adi Maulana; Jian Wang; Xiu-Zheng Zhang; Xin Ma; Qiang Wang; Xi-Jun Liu; Gong-Jian Tang (Chemical Geology, 2026)

Temporal dynamics and environmental controls of carbon and nitrogen stabilization in soil aggregates during afforestation on the Loess Plateau - Xin Qin; Weibo Kong; Zhao Peng; Liangchen Guo; Xinyi Feng; Nannan Ge; Liping Qiu; Mingan Shao; Guohua Rong; Xiaorong Wei (Soil Biology and Biochemistry, 2026)

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

A Bayesian network approach to cognitive alignment and trust in human–unmanned ship collision avoidance - Jian Zheng; Yicong Guo; Wuyue Rong; Wei Zhou; Xinlong Wang; Xucun Qi (Ocean Engineering, 2025)

Cambrian intermediate-felsic rocks in Central Pamir: Insights into source heterogeneity and subduction initiation in the Proto-Tethys Ocean - Sharifjon Odinaev; Jovid Aminov; Gennadiy Kallistov; Xin Ma; Guo-Rong Tang; Murodov Azamdzhon; Aleksandr S. Stepanov; Ilhomjon Oimuhammadzoda; Mustafo Gadoev; Sohibnazar Ashuraliev; Wei Dan; Gong-Jian Tang (Lithos, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Limonoids and protolimonoid from Swietenia macrophylla - Yun-Peng Sun; Wen-Fang Jin; Ze-Rong Xu; Ying-Wei Liu; Li-Juan Sun; Yang Yu; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

A BrDof2.4-BrHDA6 module is involved in ABA-CTK-mediating leaf yellowing in Chinese flowering cabbage by affecting histone H3 and H4 acetylation of CCGs - Zhen-liang Mou; Lei Yan; Zong-li Liu; Xin-guo Su; Ze-xiang Zeng; Yuan Rong; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Wei Wei; Jia Si (Postharvest Biology and Technology, 2025)

A ZnO packaged MEMS hydrogen sensor for reliable SIBO breath analysis with anti-H2S interference - Zheng Yang; Qian Rong; Wei Zhang; Xintao Fan; Mengen Shao; Jiang Li; Chunchang Wang; Youmin Guo (Chemical Engineering Journal, 2025)

Residual polyacrylamide-induced membrane fouling in short-flow coagulation-ultrafiltration: Behavior and mechanism - Mohan Wei; Yaozhong Zhang; Xing Zheng; Chi Zhang; Jiheng Duan; Kai Guo; Menghan Wang; Dongfei Li; Tianshuo Huang; Rong Chen (Chemical Engineering Journal, 2025)

The development of biological soil crusts shifts the drivers of soil multifunctionality in drylands - Mingming Wang; Boyi Song; Benfeng Yin; Ye Tao; Jing Zhang; Xiaoying Rong; Yonggang Li; Shihang Zhang; Zihan Kan; Yongxing Lu; Hao Guo; Xing Guo; et al. (CATENA, 2025)

One-pot construction of monodisperse core-shell silica microsphere with quinine-containing hybrid fibrous shell for racemates separation - Chenyang Wang; Tiantian Guo; Rong Li; Shujuan Ma; Yinmao Wei; Junjie Ou (Analytica Chimica Acta, 2025)

In vitro physiological and biochemical responses underlying salt tolerance of five turfgrass species - Zhen-Peng Wei; Yu-Ping Xiong; Jaime A. Teixeira da Silva; Jian-Rong Li; Jun-Yu Liu; Yuan Li; Zhan Bian; Xin-Hua Zhang; Guo-Hua Ma (Vegetos, 2025)

Front margin tectonic deformation characteristics of the Xu–Su arc tectonic belt and its tectonic implications - Rong-ying Zheng; Yun-sheng Yao; Jun Shen; Hao-yuan He; Chun-shan Guo; Xiao-hui Yu; Xun-ye Dai; Lu-wei Li; Xuan-kai Jiao; Zhong-yuan Yu; Zhi-tao Gao (Applied Geophysics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Elimination of antibiotic resistance genes and adaptive response of Firmicutes during chicken manure composting - Wei-Li Jia; Ben Wang; Lu-Kai Qiao; Fang-Zhou Gao; Wang-Rong Liu; Liang-Ying He; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

Genome-wide identification reveals a bZIP transcription factor modulating chlorophyll catabolism during leaf yellowing in harvested Chinese flowering cabbage - Ze-xiang Zeng; Yuan Rong; Zhong-qi Fan; Xin-guo Su; Lin Chen; Yan-chao Han; Hang-jun Chen; Wei Wei; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen (Postharvest Biology and Technology, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Corrigendum to “Stable isotope tracing reveals glucose metabolism characteristics of drug-resistant B-cell acute lymphoblastic leukemia” [Analytica Chimica Acta 1352 (2025) 343884] - Rong Hu; Zhengwei Duan; Mengyao Wang; Mengting Liu; Yaoxin Zhang; Yanxi Lu; Yuhan Qian; Enjie Wei; Jianghua Feng; Pengfei Guo; Yang Chen (Analytica Chimica Acta, 2025)

Molecular Insight Into the Hydrolysis of Phthalate Esters by a Family IV Esterase - Zhen Rong; Li‐Guo Hong; Ying‐Yi Huo; Jixi Li; Dao‐Qiong Zheng; Yang Ha; Jeffrey Fan; Xue‐Wei Xu; Yue‐Hong Wu (Environmental Microbiology, 2025)
Phthalate esters (PAEs) are prevalent environmental contaminants, with their biodegradation efficiently driven by microorganisms through ester bond hydrolysis. This study investigates the mechanism of Poc14, a novel family IV esterase, using x‐ray crystallography, bioinformatics, biochemistry and site‐directed mutagenesis. Phylogenetic analysis classifies Poc14 as a family IV esterase with conserved catalytic motifs crucial for its activity. Poc14 retains over 80% activity at 50°C for 4 h and tolerates up to 5% methanol or DMF, though surfactants like Tweens inhibit its function. Poc14 activity is independent of metal ions, and the addition of EDTA further enhances its activity by approximately 130%. The 1.8 Å crystal structure reveals a CAP domain and two substrate channels. Enzyme assays show Poc14 hydrolyses short‐chain diethyl phthalate (DEP) ( K m = 0.068 mM, V max = 9975 μM/min/mg) but not long‐chain di(2‐ethylhexyl) phthalate (DEHP) due to steric hindrance. Molecular docking assessed Poc14's potential to hydrolyse DEP and DEHP after residue mutations, resulting in the Poc14‐AAG variant. Poc14‐AAG could hydrolyse one bond of DEHP and diester bonds of DEP. Our study positions Poc14 as a promising enzyme for environmental remediation, with potential for optimising DEHP degradation and exploring dimerisation effects.

Active spermatogenesis in YY supermale common carp makes it suitable for potential control of this invasive species - Kuangxin Chen; Yi Rong; Yuanqi Guo; Mouyan Jiang; Yulai Wei; Xishuang Shan; Yongming Li; Yanlong Song; Ji Chen; Binbin Tao; Wei Hu (Aquaculture, 2025)

Fragmentation pattern-based nontargeted screening strategy uncovered novel halogenated nucleotides in drinking water - Guangrong Sun; Pei Guo; Rong Liu; Han Yeong Kaw; Wei Wang (Journal of Hazardous Materials, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Stable isotope tracing reveals glucose metabolism characteristics of drug-resistant B-cell acute lymphoblastic leukemia - Rong Hu; Zhengwei Duan; Mengyao Wang; Mengting Liu; Yaoxin Zhang; Yanxi Lu; Yuhan Qian; Enjie Wei; Jianghua Feng; Pengfei Guo; Yang Chen (Analytica Chimica Acta, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Petrogenesis and age of granitoids associated with the Dongshan Cu polymetallic deposit, East Kunlun Orogenic Belt, NW China: Implications for the Middle to Late Triassic tectonic setting and Cu polymetallic mineralization - Yi-Chen Chen; Zheng-Jiang Ding; Jun-Wei Bo; Shi-Jiong Han; Ting-Ting Li; Pan Ji; Rong-Qiang Guo (Geochemistry, 2025)

Multi-Omics Exploration of Obesity Biomarkers in Sedentary and Weight Loss Cohorts - Hui Wang; Yixiao Zhuang; Rong Hua; Ting Yao; Kaiqing Lin; Yitao Zhang; Rui Huang; Ruwen Wang; Shanshan Guo; Qiwei Shen; Yikai Shao; Wei Wu; et al. (Phenomics, 2025)

Design, synthesis, biological evaluation, and in silico studies of imidazo[2,1-b][1,3,4]thiadiazole derivatives as cholinesterase inhibitors - Wen-Rong Du; Yi-Xuan Wang; Xue-Wei Zhou; Yong Lan; Ben-Ben Wei; Xin-Yuan Guo; Xiao-Ke Wang; Zheng-Yue Ma (Medicinal Chemistry Research, 2025)

Legume intercropping improves soil organic carbon stability in drylands: A 7-year experimental validation - Wei Wang; Meng-Ying Li; Yang Wang; Jian-Ming Li; Wei Zhang; Qin-Hui Wen; Shuang-Jin Huang; Guang-Rong Chen; Shuang-Guo Zhu; Jing Wang; Fazal Ullah; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2025)

Integrative deep learning framework predicts lipidomics-based investigation of preservatives on meat nutritional biomarkers and metabolic pathways - Wei Jia; Aiai Guo; Wenwen Bian; Rong Zhang; Xin Wang; Lin Shi (Critical Reviews in Food Science and Nutrition, 2025)

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

The effect of soil depth on stoichiometry was greater than that of elevation in Abies georgei var. Smithii forest in Southeastern Tibet, China - Si-jie Zhu; Jiang-rong Li; Bo Zhang; Fang-wei Fu; Liang-na Guo (Acta Oecologica, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Cytotoxic monoterpenoid indole alkaloids from Tabernaemontana bovina - Bang-Yin Tan; Hua Lin; Heng-Gang Zhang; Jing-Zhi Zhao; Shi-Yu Deng; Rui-Rong Guo; Xin Wei; Lan-Chun Zhang; Rong-Ping Zhang; Hao-Fei Yu (Phytochemistry, 2025)

Advancements in the development of porous nanomaterials for CO2 capture of deep decarbonization: Pore structure and chemical group optimization - Sifan Bao; Xudong Zheng; Zihuai Xu; Biao Ji; Zhouzhou Yang; Wei Sun; Lin Guo; Youming Zhu; Jinfeng Mei; Jian Rong; Zhongyu Li (Journal of Environmental Chemical Engineering, 2025)

Inhibition of electron transfer in anaerobic ammonia-oxidized granular sludge by polyethylene terephthalate microplastics and nanoplastics: A new perspective on molecular docking and molecular dynamics simulations - Chaofan Xie; Dongyue Li; Jiarui Li; Linzhu Du; Yanshuo Wu; Rong Luo; Zheng Wang; Jun Li; Yuhan Zhu; Wei Guo (Chemical Engineering Journal, 2025)

Chitooligosaccharide application enhanced the growth and phytoremediation efficiency of industrial hemp in Cd-contaminated soils - Xinlin Zhao; Yuanchang Wang; Chenyuan Wang; Wei Zhou; Da Ouyang; Shuaishuai Gao; Xiaofei Tan; Rong Huang; Yuan Guo (Bioresource Technology, 2025)

Progress in the application of Salmonella vaccines in poultry: A mini review - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2024)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

Immunoprotective effect of recombinant Lactobacillus plantarum expressing largemouth bass virus MCP on largemouth bass - Yong-Lei Yang; Rong-Rong Zhang; Jing-Yi Pang; Jun-Hong Xing; Tian-Kui Guo; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; Jian-Zhong Wang; Xin Cao; Nan Wang; et al. (Fish & Shellfish Immunology, 2024)

MOF for encapsulating ionic liquids serves as an electrocatalyst to decrease the ignition delay time of electrically controlled solid propellants - Baiquan Chen; Cailing Zhang; Zhenguo Pang; Xugang Rong; Yanli Guo; Wei He (Chemical Engineering Journal, 2024)

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Changes in secondary sexual characteristics of female red swamp crayfish (Procambarus clarkii) and relationship to ovarian development: Implications for intensive breeding of seedlings - Lirong Qin; Jinhui He; Kuan Rong; Chao Guo; Jiashou Liu; Tanglin Zhang; Wei Li (Aquaculture, 2024)

Late cretaceous intraplate magmatism in Central and South Pamir: Response to edge-driven convection - Xin Ma; Jian Wang; Wei Dan; Qiang Wang; Guo-Rong Tang; Mustafo Gadoev; Ilhomjon Oimahmadov; Murodov Azamdzhon; Sharifjon Odinaev; Gong-Jian Tang (Lithos, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

N, S-carbon quantum dots as inhibitor in pickling process of heat exchangers for enhanced performance in multi-stage flash seawater desalination - Bochuan Tan; Yan Liu; Haiqin Ren; Zhili Gong; Xin Li; Wenpo Li; Lei Guo; Rong Chen; Juxiang Wei; Qingwei Dai; Abeer A. AlObaid (Desalination, 2024)

Design, synthesis and evaluation of imidazo[1,2-a]pyrazin-8(7H)-one derivatives as acetylcholinesterase inhibitors and antioxidants - Wen-Rong Du; Ben-Ben Wei; Xin-Yuan Guo; Yong Lan; Pan-Pan Shang; Yi-Xuan Wang; Xue-Wei Zhou; Xiao-Ke Wang; Zheng-Yue Ma (Medicinal Chemistry Research, 2024)

Label-Free Detection of Programmed Death-Ligand 1 for Prognosis Using a Truncated Aptamer and SYBR Green I - Ling Li; Zheng-Ling Li; Wei Wang; Xin-Xin Long; Ping Liu; Guo-Tian Wang; Shi-Qing Sun; Rong-Lian Du (Journal of Fluorescence, 2024)

The effectiveness of gliding arc discharge plasma in sterilizing artificial seawater contaminated with Vibrio parahaemolyticus - Meng-Ru Du; Yu-yi Guo; Han-ze Wei; Yu-pan Zhu; Rong-rong Liu; Ruo-nan Ma; Fu-kun Shi; Jin-song Guo; Jie Zhuang (Journal of Hazardous Materials, 2024)

Enhanced reaction kinetics and structure integrity of Cu/F co-doped SnO2@C composite for high-performance lithium-ion batteries - Shixin Huang; Longjun Guo; Wei Liu; Chunjin Hang; Rong An; Yongfeng Li; Yanhong Tian (Chemical Engineering Journal, 2024)

Arc building and maturation of the Lombok Island, East Sunda Arc - Guo-Rong Tang; Wei Dan; Adi Maulana; Jian Wang; Xiu-Zheng Zhang; Yun-Ying Zhang; Xin Ma; Qiang Wang; Xi-Jun Liu; Gong-Jian Tang (Chemical Geology, 2024)

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Collective effects of rising average temperatures and heat events on oviparous embryos - Liang Ma; Dan‐Yang Wu; Yang Wang; Joshua M. Hall; Chun‐Rong Mi; Hong‐Xin Xie; Wei‐Jie Tao; Chao Hou; Kun‐Ming Cheng; Yong‐Pu Zhang; Ji‐Chao Wang; Hong‐Liang Lu; et al. (Conservation Biology, 2024)
Survival of the immobile embryo in response to rising temperature is important to determine a species’ vulnerability to climate change. However, the collective effects of 2 key thermal characteristics associated with climate change (i.e., rising average temperature and acute heat events) on embryonic survival remain largely unexplored. We used empirical measurements and niche modeling to investigate how chronic and acute heat stress independently and collectively influence the embryonic survival of lizards across latitudes. We collected and bred lizards from 5 latitudes and incubated their eggs across a range of temperatures to quantify population‐specific responses to chronic and acute heat stress. Using an embryonic development model parameterized with measured embryonic heat tolerances, we further identified a collective impact of embryonic chronic and acute heat tolerances on embryonic survival. We also incorporated embryonic chronic and acute heat tolerance in hybrid species distribution models to determine species’ range shifts under climate change. Embryos’ tolerance of chronic heat (T‐chronic) remained consistent across latitudes, whereas their tolerance of acute heat (T‐acute) was higher at high latitudes than at low latitudes. Tolerance of acute heat exerted a more pronounced influence than tolerance of chronic heat. In species distribution models, climate change led to the most significant habitat loss for each population and species in its low‐latitude distribution. Consequently, habitat for populations across all latitudes will shift toward high latitudes. Our study also highlights the importance of considering embryonic survival under chronic and acute heat stresses to predict species’ vulnerability to climate change.

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Enhanced anaerobic digestion performance and sludge filterability by membrane microaeration for anaerobic membrane bioreactor application - Chun-Hai Wei; Zheng-Wei Wang; Jian-Hua Dai; Kang Xiao; Hua-Rong Yu; Fang-Shu Qu; Hong-Wei Rong; Jun-Guo He; Huu Hao Ngo (Bioresource Technology, 2024)

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Index construction and real-time hazard assessment of rice sterile-type chilling injury process in Northeast China - Bilige Sudu; Kaiwei Li; Suri Guga; Teri Gele; Feng Zhi; Ying Guo; Sicheng Wei; Guangzhi Rong; Yongbin Bao; Xingpeng Liu; Jiquan Zhang (Agricultural and Forest Meteorology, 2024)

Synthesis and antifungal activity of 2,4-diacetylphloroglucinol analogues - Xi-Long Guo; Chun-Yan Zhao; Cui-Ping Zhang; Yi Zhu; Qing-Rong Wu; Yuan-Qing Zhou; Ya-Hong Fei; Fang Ge; Wei Shi (Phytochemistry Letters, 2024)

Synchronous fluorescence spectra-based machine learning algorithm with quick and easy accessibility for simultaneous quantification of polycyclic aromatic hydrocarbons in edible oils - Jia-Wen Wei; Jia-Rong He; Shi-Yi Chen; Yi-Han Guo; Xuan-Zhu Huo; Nuan Zheng; Shuo-Hui Cao; Yao-Qun Li (Food Control, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Preparation and characterization of polyvinyl alcohol/glutaraldehyde cross-linked chitosan/ε-Polylysine degradable composite film and its antibacterial effect - Shuangfeng Guo; Xiuyun Zhang; Rong Ma; Xiangzhen Ge; Huishan Shen; Wei Liang; Guoquan Zhang; Wenhao Li (Journal of Food Engineering, 2023)

Enhancing simultaneous desulfurization and denitrification efficiency of cement kiln exhaust gas via co-catalytic Fenton oxidation process - Tongsheng Zhang; Hui Peng; Rong Chen; Yiqun Guo; Jiawei Wang; Xinzhi Chen; Jiangxiong Wei; Qijun Yu (Journal of Cleaner Production, 2023)

Feeding-induced plant metabolite responses to a phoretic gall mite, its carrier psyllid and both, after detachment - Mengke Yang; Jianling Li; Haili Qiao; Kun Guo; Rong Xu; Hongshuang Wei; Jianhe Wei; Sai Liu; Changqing Xu (Experimental and Applied Acarology, 2023)

Species diversity and related ecology of chiggers on small mammals in a unique geographical area of Yunnan Province, southwest China - Yu Guo; Juan-Xiu Zhou; Xian-Guo Guo; Wen-Yu Song; Cheng-Fu Zhao; Zhi-Wei Zhang; Rong Fan; Ting Chen; Yan Lv; Peng-Wu Yin; Dao-Chao Jin (Experimental and Applied Acarology, 2023)

Cretaceous magmatic migration and flare-up in Pamir–Karakoram - Xin Ma; Wei Dan; Jian Wang; Qiang Wang; Guo-Rong Tang; Mustafo Gadoev; Ilhomjon Oimahmadov; Gong-Jian Tang (Lithos, 2023)

Icariin inhibits hypertrophy by regulation of GPER1 and CaMKII/HDAC4/MEF2C signaling crosstalk in ovariectomized mice - Wenxia Zhao; Xiaoli Shan; Xueqin Li; Shuang Lu; Lei Xia; Huihua Chen; Chen Zhang; Wei Guo; Ming Xu; Rong Lu; Pei Zhao (Chemico-Biological Interactions, 2023)

Characterization of the fragmented mitochondrial genome of domestic pig louse Haematopinus suis (Insecta: Haematopinidae) from China - Rong Li; Yu Nie; Yi-Tian Fu; Yuan-Ping Deng; Wei Wang; Ping-Ping Ma; Guo-Hua Liu (Systematic Parasitology, 2023)

Phloroglucinol derivatives, coumarins and an alkaloid from the roots of Evodia lepta Merr. - Xiao-Ying Ding; Jun-Ru Wen; Wei-Yao Lin; Guo-Yong Huang; Qian Feng; Lixin Duan; Shi-Jie Zhang; Zhongqiu Liu; Rong-Rong Zhang; Ying Wang (Phytochemistry, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

Experimental investigation of the seismic resistance of RC beam–column connections after freeze–thaw cycle treatment - Xian-Liang Rong; Lei Li; Wei-Yuan Huang; Li-Guo Dong; Shan-Suo Zheng; Feng Wang; Dong Lu; Jun-Yan Wang (Engineering Structures, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Ejiao peptide-iron chelates regulate the metabolism of iron deficiency anemia mice and improve the bioavailability of iron - Xiang-Rong Cheng; Yu-Yao Chen; Cong-Cong Cao; Jia-Hui Ma; Chen-Xi Zhang; Zi-Wei Zhao; Qian Wu; Yuan-Yuan Li; Mitchell N. Muskat; Guo-Qing Wu (Food Bioscience, 2023)

Chemical constituents from the pericarps of Zanthoxylum bungeanum Maxim. and their chemotaxonomic significance - Bang-Yin Tan; Cai-Feng Ding; Rui-Rong Guo; Jing-Zhi Zhao; Di-Wei Ma; Kun Fan; Lan-Chun Zhang; Rong-Ping Zhang; Wei-Yan Hu; Hao-Fei Yu (Biochemical Systematics and Ecology, 2023)

Corrigendum to “Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels” [Food Hydrocolloids 139 (2023) 108527] - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Preparation and mechanism of carbon felt supported iron trioxide and zero-valent iron for enhancing anaerobic digestion performance - Zheng-Wei Wang; Chun-Hai WEI; Hua-Rong Yu; Fang-Shu Qu; Hong-Wei Rong; Jun-Guo He; Guang-Li Liu; Xia Huang; Huu Hao Ngo (Chemical Engineering Journal, 2023)

Spatiotemporal characteristics of high winds in Jilin Province during 1982–2021 - Xiao Wei; Kaiwei Li; Yunmeng Zhao; Yueting Yang; Guangzhi Rong; Ying Guo; Jiquan Zhang (International Journal of Climatology, 2023)
High winds are a type of catastrophic weather characterized by wind speeds over 10.8 m·s −1 , occurring in all seasons, and have become more frequent, impacting crop growth, agricultural production and quality of life. It is crucial to understand the spatial and temporal distribution patterns of high winds, as well as their speed and other characteristics, for logical planning of agricultural production and the creation of disaster resilience measures. This study applied the climate tendency, accumulative anomalies, theory of run, Mann–Kendall trend and Theil–Sen median to analyse the spatial and temporal distribution characteristics of the average wind speed and high wind days in Jilin Province, the probability of occurrence of high winds of various magnitudes in different eras, and the gale concentration degree (GCD) throughout Jilin Province for a total of 40 years from 1982 to 2021. The average wind speed and number of high wind days in Jilin Province have decreased over the past 40 years, and this trend has slowed over time. The average GCD in Jilin Province has shown an increasing trend over the last 40 years, with the average GCD being highest in Liouhe and lowest in Linjiang. In general, level six high winds were the main wind hazard level in Jilin Province, with the highest frequency occurring in different seasons and decades. In addition, the occurrence of high wind days is affected by global climate change and different underlying surfaces, which leads to maize and yield reduction. Research on the spatiotemporal distribution of high winds can provide important suggestions for the prevention and management of high wind disasters.

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

Chinese version of the auditory verbal learning test: normative study and clinical applications in Chinese-speaking population in Shijiazhuang city - Fang-Ming Dong; Wei Wang; Shang-Zun Guo; Kai Shao; Ya-Xue Song; Ning Han; Yan-Li Jia; Rong-Fang Feng; Jian-Hua Wang (Acta Neurologica Belgica, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Distinct responses and range shifts of lizard populations across an elevational gradient under climate change - Zhong‐Wen Jiang; Liang Ma; Chun‐Rong Mi; Shi‐Ang Tao; Fengyi Guo; Wei‐Guo Du (Global Change Biology, 2023)
Ongoing climate change has profoundly affected global biodiversity, but its impacts on populations across elevations remain understudied. Using mechanistic niche models incorporating species traits, we predicted ecophysiological responses (activity times, oxygen consumption and evaporative water loss) for lizard populations at high‐elevation (

Astaxanthin, bile acid and chlorogenic acid attenuated the negative effects of high-fat diet on the growth, lipid deposition, and liver health of Oncorhynchus mykiss - Wei Zhao; Rong Yao; Han-Lin Wei; Yu-Cai Guo; An-Qi Chen; Bao-Yang Chen; Jin-Niu (Aquaculture, 2023)

Mechanism of natural antioxidants regulating advanced glycosylation end products of Maillard reaction - Wei Jia; Aiai Guo; Rong Zhang; Lin Shi (Food Chemistry, 2023)

Achieving ultrahigh energy storage properties with superior stability in novel (Ba(1-)Bi )(Ti(1-)Zn0.5Sn0.5)O3 relaxor ferroelectric ceramics via chemical modification - Ming Yin; Guang-Jian Bai; Peng Li; Ji-Gong Hao; Wei Li; Wei-Fang Han; Yu-Chao Li; Chun-Ming Wang; Guo-Rong Li; Peng Fu (Chemical Engineering Journal, 2023)

Pipeline positioning by the surface-to-borehole electromagnetic induction method in a clayey deposit - Guo-Wei Li; Zhi-Ming Ye; Yang Zhou; Guan-Jun He; Guang-Yu Liu; Xin-Rong He (Applied Geophysics, 2023)

Proactive therapeutic drug monitoring of vincristine in pediatric and adult cancer patients: current supporting evidence and future efforts - Chun-Ying Wu; Guan-Ting Li; Chen-Chao Chu; Hong-Li Guo; Wei-Rong Fang; Tao Li; Yong-Ren Wang; Jing Xu; Ya-Hui Hu; Li Zhou; Feng Chen (Archives of Toxicology, 2023)

Personalizing atomoxetine dosing in children with ADHD: what can we learn from current supporting evidence - Di Fu; Hong-Li Guo; Ya-Hui Hu; Wei-Rong Fang; Qian-Qi Liu; Jing Xu; Dan-Dan Wu; Feng Chen (European Journal of Clinical Pharmacology, 2023)

Zinc finger protein 671 has a cancer-inhibiting function in colorectal carcinoma via the deactivation of Notch signaling - Yan Wang; Fen-rong Chen; Chong-cao Wei; Lin-lang Sun; Chen-yu Liu; Long-bao Yang; Xiao-yan Guo (Toxicology and Applied Pharmacology, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)

Study on the Relationship Between Diet, Physical Health and Gut Microflora of Chinese College Students - Xiafen Hu; Jiaqi Guo; Jiadun Wang; Wanxin Liu; Xiaochen Xiang; Siyang Chen; Xinquan Li; Jinhan Tang; Wei Zhang; Hui Chen; Rong Shu; Qingming Wu; et al. (Current Microbiology, 2022)

Neural mechanisms underlying empathy during alcohol abstinence: evidence from connectome-based predictive modeling - Guanzhong Yao; Luqing Wei; Ting Jiang; Hui Dong; Chris Baeken; Guo-Rong Wu (Brain Imaging and Behavior, 2022)

Establishment of a novel myocarditis mouse model based on cyclosporine A - Tian Hao Zhao; Yi Xuan Jiang; Kai Qin Chen; Dan Qiu; Yan Zhe Xu; Chun Ye; Ting Ren; Bo Zhang; Bin Dai; Jue Hu; Jun Lu; Fang Liang Zhou; et al. (Genes & Genomics, 2022)

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

Development of UPLC-MS/MS method for determining hainanmycin in foods of animal origin - Ke-xin Chi; Hang Yu; Ya-hui Guo; Yu-liang Cheng; Yun-fei Xie; Wei-rong Yao (Food Additives & Contaminants: Part A, 2022)

Impact of heat stress on milk yield, antioxidative levels, and serum metabolites in primiparous and multiparous Holstein cows - Xue Chen; Jia Nan Dong; Ji Ye Rong; Jun Xiao; Wei Zhao; Natnael D. Aschalew; Xue Feng Zhang; Tao Wang; Gui Xin Qin; Zhe Sun; Yu Guo Zhen (Tropical Animal Health and Production, 2022)

Wuzi Yanzong pill attenuates MPTP-induced Parkinson’s Disease via PI3K/Akt signaling pathway - Wei Hang; Hui-jie Fan; Yan-rong Li; Qi Xiao; Lu Jia; Li-juan Song; Yao Gao; Xiao-ming Jin; Bao-guo Xiao; Jie-zhong Yu; Cun-gen Ma; Zhi Chai (Metabolic Brain Disease, 2022)

How do precipitation events modify the stable isotope ratios in leaf water at Lhasa on the southern Tibetan Plateau? - Yong Wang; Wusheng Yu; Lun Luo; Minghui Li; Xiaoming Liu; Rong Guo; Yaoming Ma; Baiqing Xu; Guangjan Wu; Chengyi Zhao; Zhaowei Jing; Feili Wei; et al. (Isotopes in Environmental and Health Studies, 2022)

Bioactive isocoumarins isolated from a mangrove-derived fungus Penicillium sp. MGP11 - Rong-Qing Mei; Bin Wang; Wei-Nv Zeng; Guo-Lei Huang; Guang-Ying Chen; Cai-Juan Zheng (Natural Product Research, 2022)

Digoxin Ameliorates Glymphatic Transport and Cognitive Impairment in a Mouse Model of Chronic Cerebral Hypoperfusion - Jie Cao; Di Yao; Rong Li; Xuequn Guo; Jiahuan Hao; Minjie Xie; Jia Li; Dengji Pan; Xiang Luo; Zhiyuan Yu; Minghuan Wang; Wei Wang (Neuroscience Bulletin, 2022)

The adsorption mechanism of CF4 on the surface of activated carbon made from peat and modified by Cu - Rong Pan; Wei Dong; Yanni Guo; Yining Tang; Jun Shang; Lei Zhou; Deliang He (Environmental Science and Pollution Research, 2022)

Control of chronic obstructive pulmonary disease in urban populations: findings from a cross-sectional prevalence survey in Shenzhen, China - Le-Cai Ji; Jin-Feng Yin; Chun-Rong Lu; Hong-Yun Guan; Wei-Guo Tan; Ling-Wei Wang; Qi Jiang (Environmental Science and Pollution Research, 2022)

Infestation and distribution of mites on the Yunnan red-backed vole (Eothenomys miletus) in Yunnan Province of southwest China between 2001 and 2015 - Rong Xiang; Xian-Guo Guo; Tian-Guang Ren; Cheng-Fu Zhao; Rong Fan; Zhi-Wei Zhang; Ke-Yu Mao; Pei-Ying Peng; Xiao-Bin Huang; Ti-Jun Qian (Biologia, 2022)

The chemical profile and biological activity of different extracts of Sapindus mukorossi Gaertn. against Cutibacterium acnes - Min-Ping Wei; Jin-Dan Qiu; Lu Li; Yun-Fei Xie; Ya-Hui Guo; Hang Yu; Yu-Liang Cheng; He Qian; Wei-Rong Yao (Natural Product Research, 2021)

Isolation of two sesquiterpene glycosides from Sapindus mukorossi Gaertn. with cytotoxic properties and analysis of their mechanism based on network pharmacology - Min-ping Wei; Xiao-wen Zhu; Hang Yu; Yun-fei Xie; Ya-hui Guo; Yu-liang Cheng; He Qian; Wei-rong Yao (Natural Product Research, 2021)

Effective connectivity predicts cognitive empathy in cocaine addiction: a spectral dynamic causal modeling study - Luqing Wei; Guo-Rong Wu; Minghua Bi; Chris Baeken (Brain Imaging and Behavior, 2021)

Genome-wide identification and characterization of long non-coding RNAs involved in flag leaf senescence of rice - Xiaoping Huang; Hongyu Zhang; Qiang Wang; Rong Guo; Lingxia Wei; Haiyan Song; Weigang Kuang; Jianglin Liao; Yingjin Huang; Zhaohai Wang (Plant Molecular Biology, 2021)
Key message This study showed the systematic identification of long non-coding RNAs (lncRNAs) involving in flag leaf senescence of rice, providing the possible lncRNA-mRNA regulatory relationships and lncRNA-miRNA-mRNA ceRNA networks during leaf senescence. Abstract LncRNAs have been reported to play crucial roles in diverse biological processes. However, no systematic identification of lncRNAs associated with leaf senescence in plants has been studied. In this study, a genome-wide high throughput sequencing analysis was performed using rice flag leaves developing from normal to senescence. A total of 3953 lncRNAs and 38757 mRNAs were identified, of which 343 lncRNAs and 9412 mRNAs were differentially expressed. Through weighted gene co-expression network analysis (WGCNA), 22 continuously down-expressed lncRNAs targeting 812 co-expressed mRNAs and 48 continuously up-expressed lncRNAs targeting 1209 co-expressed mRNAs were considered to be significantly associated with flag leaf senescence. Gene Ontology results suggested that the senescence-associated lncRNAs targeted mRNAs involving in many biological processes, including transcription, hormone response, oxidation–reduction process and substance metabolism. Additionally, 43 senescence-associated lncRNAs were predicted to target 111 co-expressed transcription factors. Interestingly, 8 down-expressed lncRNAs and 29 up-expressed lncRNAs were found to separately target 12 and 20 well-studied senescence-associated genes (SAGs). Furthermore, analysis on the competing endogenous RNA (CeRNA) network revealed that 6 down-expressed lncRNAs possibly regulated 51 co-expressed mRNAs through 15 miRNAs, and 14 up-expressed lncRNAs possibly regulated 117 co-expressed mRNAs through 21 miRNAs. Importantly, by expression validation, a conserved miR164-NAC regulatory pathway was found to be possibly involved in leaf senescence, where lncRNA MSTRG.62092.1 may serve as a ceRNA binding with miR164a and miR164e to regulate three transcription factors. And two key lncRNAs MSTRG.31014.21 and MSTRG.31014.36 also could regulate the abscisic-acid biosynthetic gene BGIOSGA025169 ( OsNCED4 ) and BGIOSGA016313 (NAC family) through osa-miR5809. The possible regulation networks of lncRNAs involving in leaf senescence were discussed, and several candidate lncRNAs were recommended for prior transgenic analysis. These findings will extend the understanding on the regulatory roles of lncRNAs in leaf senescence, and lay a foundation for functional research on candidate lncRNAs.

Structural covariance of the salience network associated with heart rate variability - Luqing Wei; Guo-Rong Wu (Brain Imaging and Behavior, 2021)

Curcumin protects thymus against D-galactose-induced senescence in mice - Jie-han Li; Ting-ting Wei; Li Guo; Jia-hui Cao; Yuan-kang Feng; Shu-ning Guo; Guo-hong Liu; Yi Ding; Yu-rong Chai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Infestation and distribution of gamasid mites on Himalayan field rat (Rattus nitidus) in Yunnan Province of Southwest China - Rong Xiang; Xian-Guo Guo; Cheng-Fu Zhao; Rong Fan; Ke-Yu Mao; Zhi-Wei Zhang; Xiao-Bin Huang (Biologia, 2021)

Long-term impact of accidental pollution on the distribution and risks of metals and metalloids in the sediment of the Longjiang River, China - Qian-Li Ma; Ling-Ai Yao; Qing-Wei Guo; Guang-Jie Zhou; Rong-Chang Liang; Qiao-Li Fang; Zhen-Cheng Xu; Xue-Min Zhao (Environmental Science and Pollution Research, 2021)

Ecological analysis of gamasid mites on the body surface of Norway rats (Rattus norvegicus) in Yunnan Province, Southwest China - Zhe Liu; Xian-Guo Guo; Rong Fan; Cheng-Fu Zhao; Ke-Yu Mao; Zhi-Wei Zhang; Yue Zhao (Biologia, 2020)

Crosstalk between PKC and MAPK pathway activation in cardiac fibroblasts in a rat model of atrial fibrillation - Wei-hua Guo; Xian Wang; Mei-sheng Shang; Zhe Chen; Qi Guo; Li Li; Hai-ying Wang; Rong-hui Yu; Chang-sheng Ma (Biotechnology Letters, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Skin test of tuberculin purified protein derivatives with a dissolving microneedle-array patch - Wei Wang; Hou Ming Liu; Jing Zhou; Yu Guang Wang; Xi Feng; Hao Tang; Qinying Yan; Rong Sheng Zhu; Yu Wei Wu; Xing Guo Wang; Dan He; Fan Chen (Drug Delivery and Translational Research, 2019)

Abnormal dynamics of functional connectivity density in children with benign epilepsy with centrotemporal spikes - Rong Li; Liangcheng Wang; Heng Chen; Xiaonan Guo; Wei Liao; Ye-Lei Tang; Huafu Chen (Brain Imaging and Behavior, 2019)

Chronic stress impairs the aquaporin-4-mediated glymphatic transport through glucocorticoid signaling - Fang Wei; Jian Song; Cui Zhang; Jun Lin; Rong Xue; Li-Dong Shan; Shan Gong; Guo-Xing Zhang; Zheng-Hong Qin; Guang-Yin Xu; Lin-Hui Wang (Psychopharmacology, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Grey Matter Volumes in the Executive Attention System Predict Individual Differences in Effortful Control in Young Adults - Luqing Wei; Nana Guo; Chris Baeken; Minghua Bi; Xiaowan Wang; Jiang Qiu; Guo-Rong Wu (Brain Topography, 2019)

A Longitudinal Functional Magnetic Resonance Imaging Study of Working Memory in Patients Following a Transient Ischemic Attack: A Preliminary Study - Wei Su; Jian Guo; Yun Zhang; Jie Zhou; Ning Chen; Muke Zhou; Rong Li; Huafu Chen; Li He (Neuroscience Bulletin, 2018)

Genetic diversity and population structure of the northern snakehead (Channa argus Channidae: Teleostei) in central China: implications for conservation and management - Ruo-Jin Yan; Gui-Rong Zhang; Xiang-Zhao Guo; Wei Ji; Kun-Ci Chen; Gui-Wei Zou; Kai-Jian Wei; Jonathan P. A. Gardner (Conservation Genetics, 2018)

The accumulation and fractionation of Rare Earth Elements in hydroponically grown Phytolacca americana L. - Ming Yuan; Mei-Na Guo; Wen-Shen Liu; Chang Liu; Antony van der Ent; Jean Louis Morel; Hermine Huot; Wan-Ying Zhao; Xian-Ge Wei; Rong-Liang Qiu; Ye-Tao Tang (Plant and Soil, 2017)

Improved application of tribenuron-methyl as a chemical hybridizing agent with forchlorfenuron for rapeseed hybrid breeding - Yong-Hong Li; Dian-Rong Li; Wu-Sheng Liang; Jian-Hua Tian; Jian-Chang Li; Hao Wang; Mao-Teng Li; Xu-Peng Guo; Wen-Jie Chen; Zhen-Lan Zhang; Fei Mao; Wei-Guo Zhao (Euphytica, 2017)

Nocardia tengchongensis sp. nov., isolated from a soil sample - Shuai Li; Hong Ming; Yan-Yan Duan; Jian-Rong Huang; Zhuo-Li Zhao; Ling-Yu Zhang; Wei-Li Ji; Xiao-Lin Meng; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2017)

Association between hyperhomocysteinemia and stroke with atherosclerosis and small artery occlusion depends on homocysteine metabolism-related vitamin levels in Chinese patients with normal renal function - Guan-Hui Wu; Fan-Zhen Kong; Xiao-Feng Dong; De-Feng Wu; Qian-Zhu Guo; Ai-Rong Shen; Qing-Zhang Cheng; Wei-Feng Luo (Metabolic Brain Disease, 2017)

NaCl stress induces CsSAMs gene expression in Cucumis sativus by mediating the binding of CsGT-3b to the GT-1 element within the CsSAMs promoter - Li-Wei Wang; Mei-Wen He; Shi-Rong Guo; Min Zhong; Sheng Shu; Jin Sun (Planta, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Isolation and characterization of twenty-one polymorphic microsatellite loci from Schizothorax o’connori and cross-species amplification - XIANG-ZHAO GUO; GUI-RONG ZHANG; KAI-JIAN WEI; SHAN-SHAN GUO; JIAN-HUI QIN; Jonathan P. A. GARDNER (Journal of Genetics, 2016)

The unique origin of orange carrot cultivars in China - Zhen-Guo Ma; Xiao-Ping Kong; Li-Jie Liu; Cheng-Gang Ou; Ting-Ting Sun; Zhi-Wei Zhao; Zeng-Jian Miao; Jun Rong; Fei-Yun Zhuang (Euphytica, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Downregulation of ubiquitin-specific protease 14 (USP14) inhibits breast cancer cell proliferation and metastasis, but promotes apoptosis - Lianxin Zhu; Shuyun Yang; Song He; Fulin Qiang; Jing Cai; Rong Liu; Changjiang Gu; Zengya Guo; Chen Wang; Wei Zhang; Chunhui Zhang; Yingying Wang (Journal of Molecular Histology, 2016)

The meso-mechanism study of gypsum rock weakening in brine solutions - Wei Dong Yu; Wei Guo Liang; Yan Rong Li; Yan Mei Yu (Bulletin of Engineering Geology and the Environment, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

Transcriptome analysis reveals the potential contribution of long noncoding RNAs to brown adipocyte differentiation - Liang hui You; Li jun Zhu; Lei Yang; Chun mei Shi; Ling xia Pang; Jun Zhang; Xian wei Cui; Chen bo Ji; Xi rong Guo (Molecular Genetics and Genomics, 2015)

Heavy metals in wild marine fish from South China Sea: levels, tissue- and species-specific accumulation and potential risk to humans - Jin-Ling Liu; Xiang-Rong Xu; Zhen-Hua Ding; Jia-Xi Peng; Ming-Hua Jin; You-Shao Wang; Yi-Guo Hong; Wei-Zhong Yue (Ecotoxicology, 2015)

Paenibacillus populi sp. nov., a novel bacterium isolated from the rhizosphere of Populus alba - Tong-Yan Han; Xiao-Mei Tong; Yan-Wei Wang; Hui-Min Wang; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2015)

Longikaurin E induces apoptosis of pancreatic cancer cells via modulation of the p38 and PI3K/AKT pathways by ROS - Hai-bo Cheng; Yun Bo; Wei-xing Shen; Xian-guo Ren; Jia-ni Tan; Zhi-rong Jia; Chang-Liang Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Paenibacillus vini sp. nov., isolated from alcohol fermentation pit mud in Sichuan Province, China - Xiao-Rong Chen; Cheng-Bin Shao; Yan-Wei Wang; Ming-Xiong He; Ke-Dong Ma; Hui-Min Wang; De-Long Kong; Xiang Guo; Yi-Qing Zhou; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

The roles of IL-2 and IL-10 enhance anti-CD45RBmAb immune inhibition in allograft skin - Wei-Jian Guo; Hui Qi; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2015)

Erratum to: Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Kerui Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2015)

Reference gene selection for real-time RT-PCR normalization in rice field eel (Monopterus albus) during gonad development - Qing Hu; Wei Guo; Yu Gao; Rong Tang; Dapeng Li (Fish Physiology and Biochemistry, 2014)

Effect of two-linked mutations of the FMO3 gene on itopride metabolism in Chinese healthy volunteers - Li-Ping Zhou; Zhi-Rong Tan; Hao Chen; Dong Guo; Yao Chen; Wei-Hua Huang; Lian-Sheng Wang; Guo-Gang Zhang (European Journal of Clinical Pharmacology, 2014)

Three dimensional reconstruction of bone-cartilage transitional structures based on semi-automatic registration and automatic segmentation of serial sections - Hua Guo; Zheng-Wei Xu; Bao-Rong He; Ding-Jun Hao; Wei-Guo Bian (Tissue Engineering and Regenerative Medicine, 2014)

Isolation and characterization of nineteen novel polymorphic microsatellite loci for the northern snakehead Channa argus - Ruo-Jin Yan; Kai-Jian Wei; Xiang-Zhao Guo; Gui-Rong Zhang; Jonathan P. A. Gardner; Rui-Bin Yang; Kun-Ci Chen (Conservation Genetics Resources, 2014)

Two new bicyclic sesquiterpenes from the stems of Kadsura heteroclita - Wei Su; Jian-Ping Zhao; Jian Hu; Min Yang; Melissa Jacob; Xiong Cai; Rong Zeng; Sheng-Huang Chen; Hui-Yong Huang; Ikhlas Khan; De-An Guo; Wei Wang (Natural Product Research, 2014)

Potential Effects of Mina53 on Tumor Growth in Human Pancreatic Cancer - Xiao-ping Tan; Wei-guo Dong; Qing Zhang; Zi-rong Yang; Xiao-fei Lei; Ming-hua Ai (Cell Biochemistry and Biophysics, 2014)

Isolation and characterization of twenty-three polymorphic microsatellite loci in Schizothorax macropogon - Xiang-Zhao Guo; Gui-Rong Zhang; Ruo-Jin Yan; Wei Ji; Rui-Bin Yang; Kai-Jian Wei; Deng-Qiang Wang (Conservation Genetics Resources, 2014)

Development and characterization of 20 polymorphic microsatellite loci for the Lhasa schizothoracin Schizothorax waltoni - Xiang-Zhao Guo; Gui-Rong Zhang; Kai-Jian Wei; Wei Ji; Rui-Bin Yang; Jonathan P. A. Gardner; Qi-Wei Wei (Conservation Genetics Resources, 2014)

Cloning and identification of a novel thyroid hormone receptor β isoform expressed in the pituitary gland - Rong-Lan Zhao; Bei Sun; Ying Liu; Jing-Hua Li; Wei-Li Xiong; Dong-Chun Liang; Gang Guo; Ai-Jun Zuo; Jing-Yu Zhang (Molecular and Cellular Biochemistry, 2014)

Co-expression of the Arabidopsis SOS genes enhances salt tolerance in transgenic tall fescue (Festuca arundinacea Schreb.) - Dong-Mei Ma; Wei-Rong Xu; Hui-Wen Li; Feng-Xia Jin; Ling-Na Guo; Jing Wang; Hong-Jun Dai; Xing Xu (Protoplasma, 2014)

Isolation and characterization of fifteen polymorphic tetranucleotide microsatellite loci in Schizopygopsis younghusbandi Regan - Huan Zheng; Gui-Rong Zhang; Shan-Shan Guo; Kai-Jian Wei; Cong-Xin Xie; Tai-Ming Ge (Conservation Genetics Resources, 2013)

Isolation and characterization of twenty-four polymorphic microsatellite loci in Oxygymnocypris stewartii - Shan-Shan Guo; Gui-Rong Zhang; Xiang-Zhao Guo; Kai-Jian Wei; Jian-Hui Qin; Qi-Wei Wei (Conservation Genetics Resources, 2013)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

In vitro antifungal activity of antifungalmycin 702, a new polyene macrolide antibiotic, against the rice blast fungus Magnaporthe grisea - Zhi-Qiang Xiong; Xiao-Rong Tu; Sai-Jin Wei; Lin Huang; Xun-Hang Li; Hui Lu; Guo-Quan Tu (Biotechnology Letters, 2013)

Evaluation of Burma Reed as Substrate for Production of Pleurotus eryngii - Xian-lu Zeng; Jun-fang Lin; Li-qiong Guo; Rong-wei Cao; Wei-qiang Zeng (Indian Journal of Microbiology, 2013)

Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Keri Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2013)

Polymorphisms of UGT1A9 and UGT2B7 influence the pharmacokinetics of mycophenolic acid after a single oral dose in healthy Chinese volunteers - Dong Guo; Liang-Fang Pang; Yang Han; Hong Yang; Guo Wang; Zhi-rong Tan; Wei Zhang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Simple and rapid detection of swine hepatitis E virus by reverse transcription loop-mediated isothermal amplification - Liang-Quan Zhang; Fu-Rong Zhao; Zhi-Gang Liu; Wei-Li Kong; Heng Wang; Yun Ouyang; Huan-Bin Liang; Chao-Yi Zhang; Hai-Tao Qi; Chang-Li Huang; Si-Hu Guo; Gui-Hong Zhang (Archives of Virology, 2012)

A molecular mechanism underlying ovarian dysfunction of polycystic ovary syndrome: hyperandrogenism induces epigenetic alterations in the granulosa cells - Fan Qu; Fang-Fang Wang; Rong Yin; Guo-Lian Ding; Mohamed El-prince; Qian Gao; Bi-Wei Shi; Hui-Hui Pan; Yi-Ting Huang; Min Jin; Peter C. K. Leung; Jian-Zhong Sheng; et al. (Journal of Molecular Medicine, 2012)

At-line monitoring of key parameters of nisin fermentation by near infrared spectroscopy, chemometric modeling and model improvement - Wei-Liang Guo; Yi-Ping Du; Yong-Can Zhou; Shuang Yang; Jia-Hui Lu; Hong-Yu Zhao; Yao Wang; Li-Rong Teng (World Journal of Microbiology and Biotechnology, 2012)

Synthesis of Benzimidazoles Containing Pyrazole Group and Quantum Chemistry Calculation of Their Spectroscopic Properties and Electronic Structure - Ren Tie-gang; Cheng Hong-bin; Zhang Jing-lai; Li Wei-jie; Guo Jia; Yang Li-rong (Journal of Fluorescence, 2012)

Synthesis of novel 6-triazologlycolipids via click chemistry and their preliminary cytotoxicity assessments - Hai-Lin Zhang; Xiao-Peng He; Li Sheng; Yuan Yao; Wei Zhang; Xiao-Xin Shi; Jia Li; Guo-Rong Chen (Molecular Diversity, 2011)

Usefulness of Enhanced Power Doppler Imaging in Monitoring Acral Microcirculation in Type 2 Diabetes Mellitus and its Complications - Fang Ma; Baozhen Zhao; Huiping Zhang; Wei-Ping Li; Yuan-Yuan Liu; Yuan-Yuan Dang; Rong Wu; Le Hang Guo; Chen Lu (Cell Biochemistry and Biophysics, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

LPS pretreatment ameliorates multiple organ injuries and improves survival in a murine model of polymicrobial sepsis - Dong-Wei Shi; Jing Zhang; Hong-Ni Jiang; Chao-Yang Tong; Guo-Rong Gu; Yuan Ji; Hanssa Summah; Jie-Ming Qu (Inflammation Research, 2011)

Combination of Hyaluronic Acid Hydrogel Scaffold and PLGA Microspheres for Supporting Survival of Neural Stem Cells - Ying Wang; Yue Teng Wei; Zhao Hui Zu; Rong Kai Ju; Mu Yao Guo; Xiu Mei Wang; Qun Yuan Xu; Fu Zhai Cui (Pharmaceutical Research, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

Construction of a Tn5-Tagged Mutant Library of Xanthomonas oryzae pv. oryzicola as An Invaluable Resource for Functional Genomics - Hua-Song Zou; Liang Yuan; Wei Guo; Yu-Rong Li; Yi-Zhou Che; Li-Fang Zou; Gong-You Chen (Current Microbiology, 2011)

Quantitative estimation of the shrub canopy LAI from atmosphere-corrected HJ-1 CCD data in Mu Us Sandland - Wei Chen; ChunXiang Cao; QiSheng He; HuaDong Guo; Hao Zhang; RenQiang Li; Sheng Zheng; Min Xu; MengXu Gao; Jian Zhao; Sha Li; XiLiang Ni; et al. (Science China Earth Sciences, 2010)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

Effects of erythromycin on voriconazole pharmacokinetics and association with CYP2C19 polymorphism - Hui-Yan Shi; Jin Yan; Wen-Hui Zhu; Guo-Ping Yang; Zhi-Rong Tan; Wei-Hua Wu; Gan Zhou; Xiao-Ping Chen; Dong-Sheng Ouyang (European Journal of Clinical Pharmacology, 2010)

Effect of glycyrrhizin on the activity of CYP3A enzyme in humans - Jiang-Hua Tu; Yi-Jing He; Yao Chen; Lan Fan; Wei Zhang; Zhi-Rong Tan; Yuan-Fei Huang; Dong Guo; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2010)

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Fan-Rong Wu; Jian-Ping Li; Cheng-Wan Li; Yu Wang; Teng-Yue Zhang; Wei Hu (Molecular and Cellular Biochemistry, 2010)

Validity and reliability testing of the Chinese (mainland) version of the 39-item Parkinson’s Disease Questionnaire (PDQ-39) - Wei Luo; Xiao-hong Gui; Bo Wang; Wen-ying Zhang; Zhi-yuan Ouyang; Yi Guo; Bao-rong Zhang; Mei-ping Ding (Journal of Zhejiang University-SCIENCE B, 2010)

Phenotypic and Genetic Characteristics of Macrolide and Lincosamide Resistant Ureaplasma urealyticum Isolated in Guangzhou, China - Chun Lu; Ting lu Ye; Guo xing Zhu; Pei ying Feng; Han Ma; Rong biao Lu; Wei Lai (Current Microbiology, 2010)

Isolation and characterization of an abamectin-degrading Burkholderia cepacia-like GB-01 strain - Shinawar Waseem Ali; Rong Li; Wei-you Zhou; Ji-quan Sun; Peng Guo; Ji-ping Ma; Shun-peng Li (Biodegradation, 2010)

Identification of QTLs for yield and yield components of barley under different growth conditions - Da-wei Xue; Mei-xue Zhou; Xiao-qin Zhang; Song Chen; Kang Wei; Fan-rong Zeng; Ying Mao; Fei-bo Wu; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

Induction of cytochrome P450 2B6 activity by the herbal medicine baicalin as measured by bupropion hydroxylation - Lan Fan; Jin-Chao Wang; Feng Jiang; Zhi-Rong Tan; Yao Chen; Qing Li; Wei Zhang; Guo Wang; He-Ping Lei; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Identification of the tree shrew ATP-binding cassette transporter A1 (ABCA1) and its expression in tissues - Wu-Wei Zeng; Bing Zhou; Hui-Rong Liu; Guo-Tao Sun; Bao-Sheng Chen (Molecular Biology Reports, 2009)

An investigation on the polymorphisms of two DNA repair genes and susceptibility to ESCC and GCA of high-incidence region in northern China - Na Wang; Xiu-juan Dong; Rong-miao Zhou; Wei Guo; Xiao-juan Zhang; Yan Li (Molecular Biology Reports, 2009)

Isolation and identification of Sclerotinia stem rot causal pathogen in Arabidopsis thaliana - Ai-rong Wang; Wen-wei Lin; Xiao-ting Chen; Guo-dong Lu; Jie Zhou; Zong-hua Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Effect of fungal fusaric acid on the root and leaf physiology of watermelon (Citrullus lanatus) seedlings - Hong-sheng Wu; Xiao-ming Yin; Dong-yang Liu; Ning Ling; Wei Bao; Rong-rong Ying; Yi-yong Zhu; Shi-wei Guo; Qi-rong Shen (Plant and Soil, 2008)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Crop yield, nitrogen uptake and nitrate-nitrogen accumulation in soil as affected by 23 annual applications of fertilizer and manure in the rainfed region of Northwestern China - Sheng-Mao Yang; S. S. Malhi; Jian-Rong Song; You-Cai Xiong; Wei-Yun Yue; Li Li Lu; Jian-Guo Wang; Tian-Wen Guo (Nutrient Cycling in Agroecosystems, 2006)

Changes in Soil Microbial Community Associated with Invasion of the Exotic Weed, Mikania micrantha H.B.K - Wei-hua Li; Cong-bang Zhang; Hong-bo Jiang; Guo-rong Xin; Zhong-yi Yang (Plant and Soil, 2006)

Genetic Conservation of Hemagglutinin Gene of H9 Influenza Virus in Chicken Population in Mainland China - Jin-Hua liu; Katsunori Okazaki; Aaron Mweene; Wei-Min Shi; Qing-Min Wu; Jing-Liang Su; Guo-Zhong Zhang; Gui-Rong Bai; Hiroshi Kida (Virus Genes, 2004)

Direct plantlet regeneration from the tuber of Stachys sieboldii - Wei Li; Huan-Huan Gao; Rong Lu; Guang-Qing Guo; Guo-Chang Zheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2002)